Experimentos demostrativos para la construcción de conceptos en torno a las ondas sonoras - Gómez, Angelica; Montes, C. M. (Revista Científica, 2011)
This work stems from a research process in the classroom and covers the design, development and implementation of a classroom strategy based on demonstration experiments, for the construction of concepts about sound waves. Classroom strategy that relies on constructivist teaching led by Novak, Gowin and David Ausubel, the focus is the significant learning proposal by Ausubel. Demonstrative experiments and the working module are used as a potentially significant material for the construction of knowledge. Perhaps the teacher guides the student to bilding his learning through inserted questions. The implementation of the work realizes in the ninth grade of the school Nuestra Señorade la Salette, and finally analyzes the impact that has a classroom strategy in the learningof the students around the sounds waves.